2020
DOI: 10.3390/antibiotics10010030
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Management and Outcomes of Spondylodiscitis in Children: A Systematic Review

Abstract: Spondylodiscitis (SD) is the concurrent infection of the intervertebral disc and the adjacent vertebral bodies. Currently, there is a substantial lack of structured reviews about this topic. The aim of this study was to systematically review the available literature in order to determine the main features of pediatric SD. A systematic search of MEDLINE database was performed, according to the PRISMA guideline recommendations. Clinical features, laboratory data, radiological signs, treatments strategies, and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(90 citation statements)
references
References 38 publications
4
84
2
Order By: Relevance
“…In accordance with other studies, 6,12 in our cohort a slight male predominance was found. In larger series, a bimodal age distribution for this condition is reported, 6 while in our study a high peak of incidence in young children (<2 years) was identified, with a median age at diagnosis of 3.2 years.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In accordance with other studies, 6,12 in our cohort a slight male predominance was found. In larger series, a bimodal age distribution for this condition is reported, 6 while in our study a high peak of incidence in young children (<2 years) was identified, with a median age at diagnosis of 3.2 years.…”
Section: Discussionsupporting
confidence: 94%
“…In accordance with other studies, 6,12 in our cohort a slight male predominance was found. In larger series, a bimodal age distribution for this condition is reported, 6 while in our study a high peak of incidence in young children (<2 years) was identified, with a median age at diagnosis of 3.2 years. By dividing our cohort into 2 age subgroups, distinct clinical pictures and pathophysiological mechanisms for each were observed: older children showed a typical clinical pattern characterized by higher fever and back pain, whereas in the younger ones, symptoms were subtle and mainly included irritability, refusal to bear weight, difficulty in changing position and deterioration of general conditions.…”
Section: Discussionsupporting
confidence: 94%
“…To evaluate osteonecrosis or other bony sequelae and to guide the surgical intervention, CT scans are mandatory in PSD. Regarding the antibiotic therapy, most authors agree upon long periods—up to 6 weeks—of antibiotic therapy and bed rest ( 3 , 15 ). This treatment should lead to complete sterilization of the infected site, as to allow a “clean” surgery when needed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the current pediatric practice is derived from the management of adult spondylodiscitis (12)(13)(14) and relies upon the experience of the treating clinicians. After clinical suspicion of PSD is risen, contrast-enhanced magnetic resonance imaging is the investigation of choice for the description of the infected site location and extension (3). As this is also the most sensitive technique to detect spinal involvement, we recommend its use both in the acute phase and in the follow-up of patients with PSD.…”
Section: Considerations On Psd Managementmentioning
confidence: 99%
See 1 more Smart Citation